Biomass expansion factors for Eucalyptus globulus stands in Portugal - Soares, P.; Tomé, M. (Forest Systems, 2012)
One of several procedures for estimating carbon stocks in forests is the estimation of tree or stand biomass based on forest inventory data. The two approaches normally used to convert field measurements of trees to stand biomass values are allometric biomass equations and biomass expansion factors (BEFs). BEFs are used in published National Forest Inventory results in which biomass is not estimated or as a complement of growth models that do not include biomass predictions. In this paper, the effectiveness of BEFs for estimating total stand biomass in Portuguese Eucalyptus globulus plantations was analyzed. Here, BEF is defined as the ratio of total stand biomass (aboveground biomass plus root biomass) to stand volume with bark. To calculate total biomass, an equation was developed to estimate root biomass as a function of aboveground biomass. Changes of BEF with stand variables were analyzed. Strong relationships were observed between BEF and stand age, stand basal area, stand volume and dominant height. Consequently, an equation to predict BEF as a function of stand variables was fitted, and dominant height was selected as the predictor stand variable. Estimates of total stand biomass based on individual tree allometric equations were compared with estimates obtained with a constant BEF (0.77), used in the Portuguese National Inventory Report on Greenhouse Gases, and with estimates obtained using the dominant height-dependent BEF equation developed in this work. The BEF prediction model proposed in this work may be used to improve E. globulus Portuguese biomass estimates when tree allometric equations cannot be used.